Assessment of the genetic risks of a metallic alloy used in medical implants - Cristiano C. Gomes; Leonardo M. Moreira; Vanessa J.S.V. Santos; Alfeu S. Ramos; Juliana P. Lyon; Cristina P. Soares; Fabio V. Santos (Genetics and Molecular Biology, 2011)
The use of artificial implants provides a palliative or permanent solution for individuals who have lost some bodily function through disease, an accident or natural wear. This functional loss can be compensated for by the use of medical devices produced from special biomaterials. Titanium alloy (Ti-6Al-4V) is a well-established primary metallic biomaterial for orthopedic implants, but the toxicity of the chemical components of this alloy has become an issue of concern. In this work, we used the MTT assay and micronucleus assay to examine the cytotoxicity and genotoxicity, respectively, of an extract obtained from this alloy. The MTT assay indicated that the mitochondrial activity and cell viability of CHO-K1 cells were unaffected by exposure to the extract. However, the micronucleus assay revealed DNA damage and an increase in micronucleus frequency at all of the concentrations tested. These results show that ions released from Ti-6Al-4V alloy can cause DNA and nuclear damage and reinforce the importance of assessing the safety of metallic medical devices constructed from biomaterials.